Green central banking and regulation to foster sustainable finance - Sayuri Shirai (Asian Development Bank Institute (ADBI), 2023)
As it is becoming clear that climate change will exert a major impact on inflation, economic growth, and financial system stability, central banks and financial regulators have increasingly recognized that they can no longer ignore climate change and other environmental issues. In general, central banks are responsible for achieving price stability under the monetary policy mandate and financial stability under the macroprudential policy mandate. Therefore, it is possible for central banks to consider climate risks within their existing mandates. Moreover, the global financial markets have been facing the problems of mispricing due to the presence of low carbon prices. If these issues are unaddressed, the transition process towards a low carbon economy will remain too slow to achieve carbon neutrality. While governments play the most important role in pursuing climate policy, central banks could contribute to governments' efforts within their existing mandates. Central banks and financial regulators have begun to discuss prudential policy and take measures to cope with climate-related financial risks including climate scenario analysis and/or stress test. Moreover, there are growing discussions on how to include climate risks with respect to the capital adequacy requirements regulation for banks in the Basel framework. Central banks are also encouraged to lead by example through disclosing the impact of climate risks on central banks' own balance sheets, setting a greenhouse gas (GHG) emission reduction target on their operations, and adjusting the composition of various domestic and foreign assets held by central banks for non-monetary and monetary policy objectives. This paper provides an overview of climate-related approaches and practices undertaken by central banks and financial regulators that have become more visible in recent years.
Keywords: E52; E58; E64; 330; climate-related financial risks; climate scenario analysis; climate stress test; monetary policy; asset purchases; credit operations